REFLEKSI HUBUNGAN SOSIAL ANTARTOKOH DALAM NOVEL PADANG BULAN KARYA ANDREA HIRATA: Kajian Sosiologi Sastra - Agustin, Yoelia; Abdurahman, Abdurahman; Nursaid, Nursaid (Jurnal Bahasa dan Sastra, 2012)
The article aims to describe two things, which is: (1) reflection of social relationship inter figure in novel Padang Bulan by Andrea Hirata, and (2) reflection of social relationship inter figure and other society in novel Padang Bulan by Andrea Hirata. The data of this article is collected by read and mark that refers to reflections of social relationship interfigure in novel Padang Bulan by Andrea Hirata. The results of this article are: First, the reflection and Social relationship among figure and other figure in novel Padang Bulan by Andrea Hirata, which is (1) the social relationship between Ikal and A Ling ( coorporation), (2) the social relationship between Ikal and his Father (contradiction), (3) the social relasionship between Ikal and Enong (coorporation), (4) the social relasionhip between Ikal and Detective M. Nur (coorporation), and (5) the social relasionship between Ikal and Zinar (competition). Second,the reflection and social relationship inter figure in other society in novel Padang Bulan by Andrea Hirata is relationship of coorporation.